1999
DOI: 10.1017/s1355838299991057
|View full text |Cite
|
Sign up to set email alerts
|

Probing the TRAP–RNA interaction with nucleoside analogs

Abstract: The trp RNA-binding Attenuation Protein (TRAP) from Bacillus subtilis binds a series of GAG and UAG repeats separated by 2-3 nonconserved spacer nucleotides in trp leader mRNA. To identify chemical groups on the RNA required for stability of the TRAP-RNA complex, we introduced several different nucleoside analogs into each pentamer of the RNA sequence 59-(UAGCC)-39 repeated 11 times and measured their effect on the TRAP-RNA interaction. Deoxyribonucleoside substitutions revealed that a 29-hydroxyl group (29-OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 54 publications
(36 reference statements)
5
39
0
Order By: Relevance
“…The tryptophan ligand is completely buried between the beta-sheets at the interface between subunits in a cavity that is largely apolar with a few polar side-chain and backbone moieties making hydrogen bond contacts to the sidechain amide and backbone amino and carboxyl groups of the tryptophan (12,14-16). The bound RNA wraps around the protein with conserved bases making specific contacts with TRAP residues (13,(16)(17)(18)(19).Until recently, limited data were available on the structure of inactivate, apo-TRAP; therefore, little was known about the allosteric mechanism of tryptophan activation of TRAP for RNAbinding. The oligomeric state of TRAP (11-mer) is not altered by tryptophan, remaining oligomeric over a wide range of concentrations (10 -6 -10 -2 M), ruling out assembly as an activation mechanism (20)(21)(22).…”
mentioning
confidence: 99%
“…The tryptophan ligand is completely buried between the beta-sheets at the interface between subunits in a cavity that is largely apolar with a few polar side-chain and backbone moieties making hydrogen bond contacts to the sidechain amide and backbone amino and carboxyl groups of the tryptophan (12,14-16). The bound RNA wraps around the protein with conserved bases making specific contacts with TRAP residues (13,(16)(17)(18)(19).Until recently, limited data were available on the structure of inactivate, apo-TRAP; therefore, little was known about the allosteric mechanism of tryptophan activation of TRAP for RNAbinding. The oligomeric state of TRAP (11-mer) is not altered by tryptophan, remaining oligomeric over a wide range of concentrations (10 -6 -10 -2 M), ruling out assembly as an activation mechanism (20)(21)(22).…”
mentioning
confidence: 99%
“…The only direct hydrogen bond to the phosphodiester backbone is a hydrogen bond to the 2Ј OH of the ribose of the third G in each repeat. This contact, which was predicted by deoxyribonucleoside substitution studies (17), explains how TRAP distinguishes RNA from DNA. As predicted, Lys37, Lys56, and Arg58 all form hydrogen bonds with the RNA.…”
Section: Trap Structurementioning
confidence: 74%
“…Nucleoside analog studies identified several important functional groups for interaction with TRAP on the second A and third G of each triplet repeat. These studies also suggested that the bases in the first position (G or U), as well as the spacer bases, are not crucial for TRAP recognition and binding (17).…”
Section: Trap Structurementioning
confidence: 98%
“…The interaction between these triplets and TRAP has been well-characterized. The crystal structure of Bacillus stearothermophilus TRAP complexed with a synthetic RNA target indicates that Lys37, Lys56, and Arg58 (KKR) form hydrogen bonds with the A and the G residues in the second and third positions of the triplet repeat (Antson et al 1999;Elliott et al 1999). Gly18 and Asp39 form additional hydrogen bonds with the triplet repeats, and Phe32 likely participates in a stacking interaction (Hopcroft et al 2004).…”
Section: Introductionmentioning
confidence: 99%